PENGARUH ANALISA KEKAYAAN BERSIH WAJIB PAJAK BADAN DENGAN BEBAN PAJAK PENGHASILAN PADA KANTOR PELAYANAN PAJAK PRATAMA PALEMBANG ILIR TIMUR - Sugiharto . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
This study aimed to determine the effect of net worth corporate taxpayers with income tax expense. The study population totaled 13,195 Taxpayer, from some 13,195 taxpayers who have been categorized agency audited taxpayer is number 30, a data analysis technique used is simple linear regression. Based on the results obtained correlation coefficient number is 0568, which means that the relationship between the net worth of the income tax burden is fairly close to a strong and positive direction. While the magnitude of R Square of 0.323 means that 32.30% of total variation in Y (income tax) affected X (net worth corporate taxpayers) and the remaining 67.70% is influenced by other factors. The regression equation is: Y = X + 0.025747 547911276.770118 From the regression equation it can be interpreted that any net worth corporate taxpayers will affect income tax expense by an average of 0.02574 or by 2.57%. Keywords: Taxpayer Net Worth and Income Tax Expense